2017
DOI: 10.1016/j.jpha.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

An improved LC-MS/MS method for the quantification of alverine and para hydroxy alverine in human plasma for a bioequivalence study☆

Abstract: A highly sensitive and selective high performance liquid chromatography-tandem mass spectrometry method was developed and validated for the quantification of alverine (ALV) and its active metabolite, para hydroxy alverine (PHA), in human plasma. For sample preparation, solid phase extraction of analytes was performed on Phenomenex Strata-X cartridges using alverine-d5 as the internal standard. The analytes were separated on Symmetry Shield RP18 (150 mm×3.9 mm, 5 µm) column with a mobile phase consisting of ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The study confirmed previous observations that pharmacokinetic variability of parent alverine far exceeds the expectations one would get upon review of literature data, albeit from studies conducted on Indian population (Gomes et al, 2009;Ghosh et al, 2010;Seelam et al, 2015;Rathod et al, 2017). The metabolic process most susceptible to outlying performance in Caucasian population was found to be hydroxylation to the active metabolite 4-hydroxy alverine.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The study confirmed previous observations that pharmacokinetic variability of parent alverine far exceeds the expectations one would get upon review of literature data, albeit from studies conducted on Indian population (Gomes et al, 2009;Ghosh et al, 2010;Seelam et al, 2015;Rathod et al, 2017). The metabolic process most susceptible to outlying performance in Caucasian population was found to be hydroxylation to the active metabolite 4-hydroxy alverine.…”
Section: Discussionsupporting
confidence: 88%
“…Clinical efficacy data on alverine alone or in combination with simethicone is freely available (Wittmann et al, 2010;Martínez-Vázquez et al, 2012;Ducrotte et al, 2014). The sparse information regarding the metabolism of alverine available in scientific literature is solely centered on the pharmacokinetics of the parent compound and the active metabolite 4-hydroxy alverine (Gomes et al, 2009;Ghosh et al, 2010;Seelam et al, 2015;Rathod et al, 2017) and is only derived from studies conducted on Indian population, where intra-subject variability of the main pharmacokinetic parameters of the parent compound seems quite low based on the required sample size for successful demonstration of bioequivalence between distinct oral dosage forms.…”
Section: Introductionmentioning
confidence: 99%